Penggunaan Smartphone dan Problematik Smartphone Use pada Mahasiswa - Sunario, Sunario; Purnomo, Jusuf Tjahjo (Universitas Muhammadiyah Metro, 2023)
Problematic Smartphone Use (PSU) is when someone cannot control their smartphone use and is uncomfortable when not using it. The purpose of his study is to describe the correlation between smartphone use and Problematic Smartphone Use (PSU) in early adulthood. The population in this study was 74 people consisting of 21 male and 53 female students aged 18 - 24 years old and owning a smartphone. The research method that employs is quantitative with a correlational design. Data was collected using Smartphone Usage Questionnaire General and Absent Minded (SUQ-G&A) developed by Marty-Dugas and Problematic Mobile Phone Use Scale (PMPUS) questionnaire developed by PamukAtli compiled into the Google Form apps, and smartphone for as long as 49 hours per week are individuals with PMPUS according to the validity and the reliability correlation between Smartphone Use and PSU (r= 0.920 & = 0.000) and screentime data log as additional data to measure the duration of smartphone use. Individuals who own a smartphone can access their smartphone data log through the digital well-being feature to increase individual awareness of smartphone use so that it does not become problematic.